1995
DOI: 10.3354/dao020207
|View full text |Cite
|
Sign up to set email alerts
|

The functional cytology of Bonamia sp. (Haplosporidia) infecting oysters Tiostrea chilensis:an ultracytochemical study

Abstract: Bonamia sp., a serious pathogen of oysters Tiostrea chilensis, was studied using the zinc iodide-osmium tetroxide technique (ZIO), the imidazole-osmium technique for lipids (IM), and reactivity for acid phosphatases [P-glycerophosphatase (P-GPase), cytidine monophosphatase at pH 5.0 (CMPase 5.0) and pH 2.7 (CMPase 2.7), thiamine pyrophosphatase (TPPase)], and P-galactosidase to try and determine the function of cytoplasmic organelles. Z10 reacted with the nuclear membrane, Golgi, endoplasmic reticulum (ER), cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 8 publications
2
33
0
Order By: Relevance
“…The inclusion bodies in H. ascidiarum (Ormières & de Puytorac 1968, Ciancio et al 1999) may also correspond to DVs, but their association with surrounding ER is similar to that seen around lipid droplets in Bonamia exitiosa (= Bonamia sp.) (Hine & Wesney 1994). However, they are also closely associated with the spherulosome, as are DVs, so their identity is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion bodies in H. ascidiarum (Ormières & de Puytorac 1968, Ciancio et al 1999) may also correspond to DVs, but their association with surrounding ER is similar to that seen around lipid droplets in Bonamia exitiosa (= Bonamia sp.) (Hine & Wesney 1994). However, they are also closely associated with the spherulosome, as are DVs, so their identity is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Haemocyte containing extensive membranous whorls; uninucleate stages of parasites can be seen in various states of degeneration within these whorls (arrows); scale bar = 2 µm 1975b), and granular material may lie in pits on the nuclear surface (Perkins 1969, Hine & Wesney 1992. Cytoplasmic organelles include lipid droplets (Hine & Wesney 1994), sparse endoplasmic reticulum (ER) and ribosomes, haplosporosomes or homologous structures, and nuclear membrane-bound Golgi (NBG) (Perkins 1979, Hine & Wesney 1992.…”
Section: Discussionmentioning
confidence: 99%
“…The reticulated structure (Hine & Wesney 1992), which may be connected to anastomosing endoplasmic reticulum (Hine & Wesney 1994a), and the Golgi associated with lipoid body genesis (Hine & Wesney 1994a) have not been described in B. ostreae. However, the cylindrical confronting cister- Tetra-nucleate plasmodia were rare in this study, but multi-nucleated and diplokaryotic plasmodia appear more developed in Bonamia ostreae (Brehélin et al 1982), particularly if the stages observed by Bonami et al (1985) are those of B. ostreae.…”
Section: Comparison With Bonamia Ostreaementioning
confidence: 99%
“…(Hine 1991a,b, Hine & Wesney 1994a, Mikrocytos spp. (Farley et al 1988), and haplosporosome-bearing parasites of crabs (Newman et al 1976) and shrimps (Dykovå et al 1988) has been regarded as uncertain as they lack a known spore stage and, on this basis, Bonamia spp.…”
Section: Ultrastructural Studiesmentioning
confidence: 99%
See 1 more Smart Citation